Scheduling strategy of a cloud-based virtual energy storage system (VESS) for achieving energy saving - Lau, Sim Yee (2024)
This project emphasizes on seting up an Internet of Things (IoT) monitoring system and scheduling a strategy for the cloud-based virtual energy storage system (VESS) to achieve energy saving. As the cost of energy storage system (ESS) remained high, the application of VESS emerges as a financially viable alternative to manage the energy consumption of flexible loads like air conditioner to reduce the energy usage. This is due to the fact that when the air conditioner toggles one degree higher or lower, it behaves like the charging and discharging of an ESS since the energy consumed will be increased or decreased. The research explores a review of the literature on limitation of ESS, concepts of VESS, role of cloud computing and IoT in VESS as well as the control strategy algorithm. Furthermore, different case studies are conducted to investigate the load profile of the cooling system during both raining and summer seasons. Besides, the case studies also underscore the performance analysis of the PID and Fuzzy PID control algorithms. The results show that the cooling system consume higher energy in the summer season due to the greater ambient temperature. However, the energy consumption of the cooling system can be saved within the range of 17.13 % to 44.9 % and 11.91 % to 44.12 % by utilizing the PID and Fuzzy PID controllers respectively. In addition, the analysis suggests that Fuzzy PID controller contributes to a smaller rise time and higher stability in maintaining the appropriate indoor temperature when compared to PID controller. Overall, the findings highlight that the application of VESS plays a crucial role in managing energy consumption in an economical and effective manner.